Are Cybersecurity Professionals Satisfied with Recent Cybersecurity Graduates? (Journal of The Colloquium for Information Systems Security Education, 2020)
This pioneering research project examines the expectations of cybersecurity professionals in terms of contentment with recent graduates. In particular, the project sought to determine the professionals' satisfaction with recent hires of undergraduate graduates. Overall, 73% of the participants indicated satisfaction with recent cybersecurity graduates. In addition, 67% of these professionals believed that recent graduates had a satisfactory level of competency.
Keywords: cybersecurity; graduates; employer; expectations